2005
DOI: 10.1128/jb.187.18.6509-6516.2005
|View full text |Cite
|
Sign up to set email alerts
|

The pCoo Plasmid of Enterotoxigenic Escherichia coli Is a Mosaic Cointegrate

Abstract: CS1 is the prototype of a class of pili of enterotoxigenic Escherichia coli (ETEC) associated with diarrheal disease in humans. The genes encoding this pilus are carried on a large plasmid, pCoo. We report the sequence of the complete 98,396-bp plasmid. Like many other virulence plasmids, pCoo is a mosaic consisting of regions derived from multiple sources. Complete and fragmented insertion sequences (IS) make up 24% of the total DNA and are scattered throughout the plasmid. The pCoo DNA between these IS eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…(124). The composite regions of pCoo are separated by IS100-associated direct repeats, suggesting that a recombination event occurring between regions of two different plasmids resulted in the formation of the cointegrate pCoo (62). The key feature identified on this plasmid was the polycistronic coo operon, which contains four genes encoding the CS1 pilus.…”
Section: Human Etec Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…(124). The composite regions of pCoo are separated by IS100-associated direct repeats, suggesting that a recombination event occurring between regions of two different plasmids resulted in the formation of the cointegrate pCoo (62). The key feature identified on this plasmid was the polycistronic coo operon, which contains four genes encoding the CS1 pilus.…”
Section: Human Etec Plasmidsmentioning
confidence: 99%
“…Some of the original designations have been replaced by newer nomenclature (i.e., CFA/III is CS8, and the PCF types have all been replaced by CS types), whereas others have retained their original names (i.e., CFA/I) (64). Plasmid pCoo was the first completely sequenced human ETEC CF-encoding plasmid (62). pCoo was isolated from human ETEC strain C921b-1, which is known to express CS1 and CS3 (143).…”
Section: Human Etec Plasmidsmentioning
confidence: 99%
“…The CFA/I, CS1, CS2, CS4, CS5, CS14, CS17, CS19, and PCF071 antigens of human enterotoxigenic E. coli isolates are carried by plasmids (8,60,89,92,97,98,120,219,270,308,358). The presence of these fimbrial antigens in human isolates is thought to reflect their selective binding to human tissue (102).…”
Section: The Alternate Chaperone/usher Familymentioning
confidence: 99%
“…Nine features were identified that were exclusively present in both neobladder isolates (Table 5). All nine of these features are similar to those encoded on the ETEC plasmid pCOO (Froehlich et al, 2005). These genes are all from a type IV secretion apparatus known as the R64 thin pilus, which is utilized in liquid-based conjugations (Kim & Komano, 1997).…”
Section: Hybridization Features Exclusive To the Neobladder Isolatesmentioning
confidence: 83%
“…The hybridization patterns of the unique features of the neobladder isolates (Table 5) suggested that each isolate contained at least one plasmid. The genes shared only between the neobladder isolates are part of a type IV secretion system from the pCOO plasmid in ETEC (Froehlich et al, 2005). Other genes that are specific to each of the isolates (Tables 3 and 4) are also part of plasmid transfer or replication genes, suggesting that the core of the type IV system is similar but not identical between these two plasmids.…”
Section: Discussionmentioning
confidence: 99%